Antepartum Dalteparin Versus No Antepartum Dalteparin for the Prevention of Pregnancy Complications in Pregnant Women With Thrombophilia (TIPPS): A Multinational Open-Label Randomised Trial. Issue 2 (February 2015) - Rodger, Marc A.; Hague, William M.; Kingdom, John; Kahn, Susan R.; Karovitch, Alan; Sermer, Mathew; Clement, Anne Marie; Coat, Suzette; Chan, Wee Shian; Said, Joanne; Rey, Evelyne; Robinson, Sue; et al.
Abstract : ABSTRACT: Thrombophilias are acquired or genetic predispositions to venous thromboembolism (VTE), which occurs more often in pregnant than in nonpregnant women. Placenta-mediated complications, including preeclampsia, small-for-gestational-age (SGA) infant, placental abruption, or pregnancy loss, are also more common in women with thrombophilia. Whether pregnant women with thrombophilia should receive antepartum thromboprophylaxis remains unclear. Low-molecular-weight heparin (LMWH) is the drug of choice in pregnancy for women who require anticoagulation, as it does not cross the placenta and has a low risk of major bleeding, heparin-induced thrombocytopenia, and heparin-induced osteoporosis. However, it requires daily or twice-daily subcutaneous injections, is expensive, and can complicate regional anesthetic options. This randomized trial was designed to determine whether antepartum prophylactic dalteparin, an LMWH, would reduce the risk of VTE and placenta-mediated complications in women with thrombophilia at high risk of pregnancy complications. Of 3022 screened women with prior pregnancy complications or VTE risk factors and thrombophilia, eligible parturients were assigned to antepartum dalteparin or no antepartum dalteparin (control subjects). Those in the study group received antepartum dalteparin (5000 IU) once daily by subcutaneous self-injection from the day of randomization until 20 weeks' gestation, increasing to 5000 IU twice daily from 20 weeks until 37 weeks or greater. Postpartum, all participants received 5000 IU dalteparin once daily by subcutaneous self-injection from day 1 (administered 6–28 hours after delivery) until day 42. The primary end point was a composite outcome including symptomatic major VTE, severe or early-onset (<32 weeks) preeclampsia, SGA infant, and pregnancy loss. Secondary outcomes included major and minor bleeding, bone mineral density, preterm delivery, placental abruption, heparin-induced thrombocytopenia, and symptomatic fracture. All data analyses were done with an intention-to-treat (ITT) approach. Statistical tests were 2-sided, with P < 0.05 indicating significance. Of 469 women eligible to participate, 292 were initially randomized, and 146 and 143 women, respectively, were allocated to the antepartum dalteparin and control groups. After crossovers, 148 received antepartum dalteparin, and 141 did not. The ITT analysis included 146 women in the antepartum dalteparin group and 143 in the control group; respective numbers for the on-treatment and safety analyses were 143 and 141. The 2 groups were similar in baseline characteristics. Their mean age was 31.8 ± 4.9 years, and mean gestational age at randomization was 11.9 ± 4.6 weeks. Of the total 289 women, 176 (60%) had factor V Leiden, and 63 (22%) had the prothrombin gene mutation. Sixty-one percent of the women had a prior pregnancy complication, and 44% had a risk factor for VTE. Twenty-five of 146 women in the study group (17.1%; 95% confidence interval, 11.4%–24.2%) had the primary composite outcome compared with 27 of 143 control subjects (18.9%; 95% confidence interval, 12.8%–26.3%; P = 0.70). The 2 groups did not differ in the component outcomes of the primary composite outcome. Three patients had symptomatic major VTE while taking dalteparin. Mean birth weights and gestational ages at delivery of live-born infants were similar between the groups. In the ITT and on-treatment analyses, the groups did not differ significantly in subgroup analyses for thrombophilia, previous pregnancy complications, previous VTE or risk factors, aspirin use, gestational age at enrollment, or country. Minor bleeding occurred in 19.6% of women in the antepartum dalteparin group and in 9.2% of control subjects (9.2%; P = 0.01). No patients had heparin-induced thrombocytopenia, changes in bone mineral density, or clinical fracture. Neonatal death occurred in 1 infant born prematurely in the antepartum dalteparin group and 2 in the control group. Six children exposed to antepartum dalteparin and 2 in the control group had congenital anomalies. Antepartum dalteparin did not reduce the risk of pregnancy loss, VTE, or placenta-mediated pregnancy complications in high-risk women with thrombophilia. This lack of benefit is important, and additional research is needed to determine whether LMWH reduces the risk of recurrent severe preeclampsia, severely SGA infants, or placental abruption.